554 Atrial mechanical dispersion in patients with atrial fibrillation undergoing catheter ablation: a strain study. (17th January 2020) - Katbeh, A; Balogh, Z; Stefanidis, E; De Potter, T; Geelen, P; Iliodromitis, K; Barbato, E; Van Camp, G; Penicka, M
Abstract: Background: Atrial mechanical dispersion (MD) might increase the risk of atrial fibrillation (AF). However, the data on atrial mechanical dispersion in patients with AF undergoing catheter ablation (CA) are scarce. Purpose: To describe effects of CA on inter- and left intra-atrial MD in patients with different sub-types of AF undergoing CA. Methods: We prospectively enrolled 138 symptomatic patients (age: 63 ± 21 years, 32% females) with paroxysmal AF undergoing first (81%) or redo (19%) CA during sinus rhythm, and 20 individuals (age: 66 ± 23 years, 20% females) with long-standing persistent AF undergoing first CA during AF. All patients had normal (≥50%) left ventricular ejection fraction. Control group consisted of 23 healthy controls. The atrial strain and strain rate (SR) were assessed using the two-dimensional speckle tracking echocardiography as average of segmental values in all apical views for LA and in four chamber (4CH) apical view for RA. We quantified inter-atrial MD as the standard deviation of time from the onset of the P wave to peak negative strain curves (Figure 1), and left intra-atrial MD as the standard deviation of time from the onset of QRS wave to peak positive strain curves (Figure 2) of all LA segmental components in 4CH apical view after setting adjusting the reference frame to coincide with the onset of the QRS. Results: Figure 3 shows a time course of reservoir LA strain and left intra-atrial MD in patients with paroxysmal AF undergoing the First-CA (3A) versus the Redo-CA (3B), and in patients with long-standing persistent AF (3C). At 1-day pre-ablation, patients with long-standing persistent AF showed significantly lower reservoir strain of both atria and higher left intra-atrial MD as compared with both paroxysmal AF groups and controls (all p < 0.01). The Redo-CA versus the First-CA group showed significantly lower LA reservoir strain (p < 0.01) while left intra-atrial MD was similar. RA reservoir strain and inter-atrial MD was similar between groups with paroxysmal AF. At 1-day post-ablation, we observed a significant deterioration of reservoir LA strain and left intra-atrial MD only in the First-CA group. After 3- month follow-up, left intra-atrial synchrony was significantly improved compared with pre-ablation in both groups of paroxysmal AF undergoing the first CA and long-standing persistent AF (p < 0.05). The reservoir LA strain showed partial recovery to pre-ablation values in paroxysmal AF undergoing first-CA while it showed a continuous improvement in long-standing persistent AF. In contrast, patients with paroxysmal AF undergoing redo-CA did not show significant improvement in any of these indices. Inter-atrial MD and RA strain did not show significant improvement in either group. Conclusion: Atrial strain and MD shows distinct behavior in patients with different sub-types of AF post CA. Atrial MD may provide a complimentary information to strain when assessing LA function.